On Running’s strategy for Global Expansion and Brand Positioning - Mosiichuk, Yuliia (2025)
The purpose of this thesis is to examine the strategic growth of On Running, the company, which started as a Swiss start-up and made it to a globally recognized premium sportswear brand. By utilizing frameworks such as Porter’s Five Forces, the Ansoff Matrix, and the Uppsala Model, the study explores how On Running has leveraged its advantages for building an international presence. Despite strong fundamentals such as technologies and sustainable practices, the brand faces the lifestyle-oriented market perception instead of its intended identity as a performance-driven innovator. The findings suggest increased investment in brand awareness to support growth through targeted marketing and marketing-specific strategies. Also, primary research suggests that the Czech Republic offers a favorable environment for DTC expansion after increased brand recognition, Mexico is suggested for strengthened wholesale and e-commerce partnerships, and India represents a high-potential market for distributor-led entry.